Successful Use of Tocilizumab in a Patient with Coexisting Rheumatoid Arthritis and Ulcerative Colitis - Matthew Chak Hin Szeto; Metin Devrim Yalçın; Abdul Khan; Andrzej Piotrowicz (Case Reports in Immunology)
Tocilizumab is an interleukin-6 receptor inhibitor licensed for moderate to severe rheumatoid arthritis (RA). We report a case of Tocilizumab monotherapy for severe active RA in a patient with coexisting ulcerative colitis (UC). The patient was intolerant to multiple disease-modifying drugs, so Tocilizumab monotherapy was commenced. We found clinical improvement in both RA and UC. There was no major adverse event after 2 years. Manufacturer advised caution in using Tocilizumab in patient with gastrointestinal ulceration due to an increased risk of bowel perforation. However, alternative treatments such as glucocorticoid and nonsteroidal anti-inflammatory drugs may carry a higher bowel perforation risk. The presence of gastrointestinal ulceration therefore should not constitute an absolute contraindication for Tocilizumab therapy. Future studies of registry data will inform clinician of the Tocilizumab-related risk of gastrointestinal toxicity in “real-life” settings. Contrary to previous case report, we found Tocilizumab therapy to have a positive effect on UC. Laboratory studies supported a role for interleukin-6 in the pathophysiology of UC. Further clinical trial to evaluate the therapeutic role of Tocilizumab in UC would be warranted.